Upadacitinib for Spondyloarthritis; A new treatment option. (October 2022) - Shekha, Manahil; Shaikh, Omer Ahmed; Shaikh, Gulrukh; Ochani, Sidhant; Ullah, Kaleem
Abstract: Axial spondyloarthritis, often known as ankylosing spondylitis (AS), is an inflammatory condition that mostly affects the axial skeleton. Axial spondyloarthritis is further subdivided into non-radiographic and radiographic AS. For radiographic axial spondyloarthritis, the male-to-female ratio is two to one, while for non-radiographic axial spondyloarthritis, it is one to one, often manifesting in the third decade of life. Effective treatment for AS includes non-steroidal anti-inflammatory medications (NSAIDs) and TNF blockers. All articular symptoms of AS have been seen to improve significantly when treated with TNF inhibitors such as Etanercept, Adalimumab, Infliximab, Certolizumab, and Golimumab. Upadacitinib, has proven to be significantly efficacious in the management of active non-radiographic axial spondyloarthritis (nr-axSpA), with MRI-based or blood tests displaying objective evidence of inflammation, an increased C-reactive protein, and an unsatisfactory response to Non-steroidal anti-inflammatory drug (NSAIDs). the lack of oral therapy options, and the stigma associated with surgical intervention makes it crucial to offer an unambiguous treatment choice, especially in light of the disease's strong heredity. Thus, Upadacitinib's usage in the treatment of nr-axSpA and its clinical trial is a significant step toward the availability of an internationally-approved medicine for the treatment of nr-axSpA.